2008
DOI: 10.1143/jjap.47.2369
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Plasma Source-Dependent Charging Polarity in Metal–Oxide–Semiconductor Field Effect Transistors with High-k and SiO2 Gate Dielectrics

Abstract: Friction is ubiquitous in all aspects of everyday life and has consequently been under study for centuries. Classical theories of friction have been developed and used to successfully solve numerous tribological problems. However, modern applications that involve advanced materials operating under extreme environments can lead to situations where classical theories of friction are insufficient to describe the physical responses of sliding interfaces. Here, we review integrated experimental and computational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 90 publications
(127 reference statements)
1
25
0
Order By: Relevance
“…Owing to the effects of trapped charges in these relatively thicker high-k dielectrics, the stress current (J CVS ) of the damaged sample becomes smaller than that of no-damaged one. Thus, we speculate that this feature is induced by the effect of trapped charges during a CVS measurement [2,9]. Figs.…”
Section: Figs 1(a) 1(d)mentioning
confidence: 87%
See 2 more Smart Citations
“…Owing to the effects of trapped charges in these relatively thicker high-k dielectrics, the stress current (J CVS ) of the damaged sample becomes smaller than that of no-damaged one. Thus, we speculate that this feature is induced by the effect of trapped charges during a CVS measurement [2,9]. Figs.…”
Section: Figs 1(a) 1(d)mentioning
confidence: 87%
“…In the following, let us focus on the mechanism of the t CVS increase. It was reported [9] that the direction of V th in a high-k MOSFET depends on the amount of PCD. The number of created defects, the nature of trap sites, and the distribution of charge trapping sites determine this charging polarity.…”
Section: Figs 1(a) 1(d)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pads with a constant area of 42000 µm 2 served as antennas of the box-type structure. 23,36,37) Figure 1 shows plasma charging damage to MOSFETs. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has also been found that not only conventional MOSFETs with SiO 2 but also those with high-k films suffer from threshold voltage (V th ) shift induced by PCD. 23) The V th shift is mainly attributed to defects created by PCD in gate dielectrics and SiO 2 /Si interface states. Such created defects induce carrier trapping and detrapping.…”
Section: Introductionmentioning
confidence: 99%